EXTRAMEDULLARY DISEASE IN ACUTE PROMYELOCYTIC LEUKEMIA: TWO-IN-ONE DISEASE - Giorgina Specchia; Francesco Albano (Mediterranean Journal of Hematology and Infectious Diseases, 2011)
In acute promyelocytic leukemia (APL), extramedullary disease (EMD) is particularly rare and shows special clinical and biological features. It is estimated that about 3–5% of APL patients will suffer extramedullary relapse. The most common site of EMD in APL is the CNS. At present, there are still many issues of EMD in APL needing further clarification, including pathogenesis, risk factors, prognosis and treatment. A better understanding of the biological mechanisms underlying EMD is important to be able to devise more effective CNS prophylaxis and induction-consolidation therapeutic strategies